PEMANFAATAN VIDEO ONLINE DALAM PEMAHAMAN MATERI PREPOSITION OF TIME AND PLACE (AT, IN, ON) - Lilik Yuliawati (Universitas Muhammadiyah Surakarta, 2019)
In this high technology era, there are various media which can be used in teaching and learning activity including English Course where students feel difficult to use at, in, and on as preposition of time and place. Lecturer can combine the conventional technique through lecturing with online video playing inside and outside the classroom as the usage of e-learning concept. This research was held to know the students’ perception of online video usage in understanding Preposition of Time and Place (At, In, On) material. Descriptive method is used by using qualitative and quantitative data. Qualitative data were taken from literature review, whereas quantitative data were taken from students’ test and questionnaire results. The respondents are 100 students of Bina Sarana Informatika University majoring Information System who were randomly chosen. The result of this research shows that most of the students assume that online video is easily accessible and can help them review and understand the concept of Preposition of Time and Place (At, In, On).